The usability of new "Up Wound" technologies for monitoring diabetic patients with wounds in Basic Care: A prospective study (Research, Society and Development, 2021)
The usability of new tecnologies "up ferida" for the monitoring of diabetic patients with injuries requiring basic attention. A patented revision and library crossing a tecnological prospective. Summary: A tecnological prospective was made to evaluate the usability of new tecnologies for the monitoring of basic attention injuries. Patents and scientific articles were retrieved from databases WIPO, PATENTINSPIRATION, LATIP - SPACENET, Science Direct and Scopus, respectively. A search on the database WIPO utilizing the term "monitoring and diabetic" on the field "cover letter" and the option "name" PCT generated a return of 460 patents. No returned patents were recovered  from database LATIPAP - SPACENET when using the term "monitoring and diabetic "in the field "intelligent search". The database PATENTINSPIRATION utilizing the term "monitoring and diabetic" 1 644 patents recovered reading the integral "title" and "summary" with the code IPC and CPC A61, B1/00, thus none refer the involvement of applications for the monitoring of diabetic patients with basic attention injuries indicating inediting having of a proposal in tracking patents deposited in Brazil by PCT.